Hypersialylation and multiple myeloma - O’Dwyer, Michael; Glavey, Siobhan; McAvera, Roisin; Natoni, Alessandro; Ryan, Aideen E. (Frontiers in Hematology, 2024)
There is growing recognition of the importance of sialylation as a critical post translational modification in cancer. In this article we review the role of increased cell surface sialylation (hypersialylation) in Multiple Myeloma as it relates to cellular trafficking and immune evasion. Knowledge of the specific effects of sialic acid on cell trafficking machinery and modulation of immune cell interactions will identify opportunities for therapeutic interventions. The available evidence indicates that hypersialylation facilitates disease progression and negatively impacts on response to treatment and overall survival. Further research is required to fully elucidate the mechanisms through which hypersialylation influences disease biology and therapy resistance with the ultimate goal of developing new treatment approaches to improve the outcomes of patients with Multiple Myeloma.